The Influence of Digital Intelligence on Improving the Learning Quality of Arabic Language Courses - Afriza; Kasmiati; Halomoan; Muhammad Fadhlan (International Journal of Education and Teaching Zone, 2025)
The integration of technology in Arabic language learning remains a significant challenge, requiring lecturers to possess advanced digital competencies. This study examines the influence of digital intelligence on the quality of Arabic language instruction at the Sultan Syarif Kasim State Islamic University. Employing a quantitative ex post facto design with correlational analysis, the study involved 30 lecturers from the Arabic Language Education Study Program. Data were collected using structured questionnaires, supporting interviews, and document analysis. Results indicate a statistically significant and strong positive relationship between lecturers’ digital intelligence and the quality of learning, with a coefficient of determination of 74.3% (R² = 0.743). Linearity tests confirm a consistent linear relationship between the variables, and linear regression analysis reveals a correlation coefficient of R = 0.862, highlighting the robustness of this association. Lecturers with higher digital intelligence are better able to integrate technology into their teaching, enhance interactivity, and improve pedagogical effectiveness. These findings underscore the need for systematic and sustained initiatives to strengthen digital competencies among Arabic language lecturers. Beyond instrumental technology use, lecturers are encouraged to adopt innovative pedagogical strategies that leverage digital tools to optimize learning outcomes.